2017
DOI: 10.1016/j.coviro.2016.11.009
|View full text |Cite
|
Sign up to set email alerts
|

The elucidation of non-classical MHC class II antigen processing through the study of viral antigens

Abstract: By convention, CD4+ T cells are activated predominantly by Major Histocompatibility Complex class II-bound peptides derived from extracellular (exogenous) antigens. It has been known for decades that alternative sources of antigen, particularly those synthesized within the antigen-presenting cell, can also supply peptides but the impact on TCD4+ responses, sometimes considerable, has only recently become appreciated. This review focuses on the contributions that studies of viral antigen have made to this shift… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 73 publications
0
17
0
Order By: Relevance
“…Recent findings even show a direct loading of MHCII molecules in the ER and Golgi supported by alternative chaperones as described below 30 . Overall, a very attractive, and perhaps more realistic picture of MHCII antigen presentation will include interconnections between all these different routes and processes as proposed by the Eisenlohr lab for viral infections 31,32 (Figure 1D).…”
Section: General Mechanisms Of Antigen Presentation By Mhcii Moleculesmentioning
confidence: 86%
“…Recent findings even show a direct loading of MHCII molecules in the ER and Golgi supported by alternative chaperones as described below 30 . Overall, a very attractive, and perhaps more realistic picture of MHCII antigen presentation will include interconnections between all these different routes and processes as proposed by the Eisenlohr lab for viral infections 31,32 (Figure 1D).…”
Section: General Mechanisms Of Antigen Presentation By Mhcii Moleculesmentioning
confidence: 86%
“…Following proteolytic cleavage, these processed peptides displace CLIP on recycled MHC-II molecules, which are then transported to the cell surface for presentation to CD4 + T cells. However, considerable evidence has accumulated, suggesting that alternative pathways exist that allows cells to directly present cytosolic proteins on MHC-II (46). For example, a recent report found that dendritic cells infected with modified VacV Ankara presented MHC-II-restricted peptides from an endogenous presentation pathway to CD4 + T cells, a process that required functional proteasomes and autophagy (47).…”
Section: Discussionmentioning
confidence: 99%
“…However, TAPL may have a more specialized function in professional antigen-presenting cells, in which its expression is strongly upregulated (Demirel et al, 2007 ). There are alternative pathways of endogenous antigens for processing and loading on MHC II (Veerappan Ganesan and Eisenlohr, 2017 ). One of these pathways is proteasome dependent but TAP-independent (Dani et al, 2004 ; Miller et al, 2015 ; Thiele et al, 2015 ).…”
Section: Physiological Functionmentioning
confidence: 99%